Mesoporous thin films on graphene FETs: nanofiltered, amplified and extended field-effect sensing. Issue 45 (11th November 2021) - Alberti, Sebastián; Piccinini, Esteban; Ramirez, Pedro G.; Longo, Gabriel S.; Ceolín, Marcelo; Azzaroni, Omar
Abstract : Mesoporous thin films on graphene transistors display unique nanofiltered, amplified and extended field-effect sensing. Synergy between the molecular confinement inside mesopores and the graphene interfacial transduction allows this outcome. Abstract : The ionic screening and the response of non-specific molecules are great challenges of biosensors based on field-effect transistors (FETs). In this work, we report the construction of graphene based transistors modified with mesoporous silica thin films (MTF-GFETs) and the unique (bio)sensing properties that arise from their synergy. The developed method allows the preparation of mesoporous thin films free of fissures, with an easily tunable thickness, and prepared on graphene-surfaces, preserving their electronic properties. The MTF-GFETs show good sensing capacity to small probes that diffuse inside the mesopores and reach the graphene semiconductor channel such as H +, OH −, dopamine and H2 O2 . Interestingly, MTF-GFETs display a greater electrostatic gating response in terms of amplitude and sensing range compared to bare-GFETs for charged macromolecules that infiltrate the pores. For example, for polyelectrolytes and proteins of low MW, the amplitude increases almost 100% and the sensing range extends more than one order of magnitude. Moreover, these devices show a size-excluded electrostatic gating response given by the pore size. These features are even displayed at physiological ionic strength. Finally, a developed thermodynamic model evidences that the amplification and extended field-effect properties arise from the decrease of free ions inside the MTFs due to the entropy loss of confining ions in the mesopores. Our results demonstrate that the synergistic coupling of mesoporous films with FETs leads to nanofiltered, amplified and extended field-effect sensing (NAExFES).